Friday

April 18, 2014

April 18, 2014

Posted by **Irma** on Monday, April 5, 2010 at 4:50pm.

- algebra -
**Reiny**, Monday, April 5, 2010 at 4:53pmln(3x-4)-Ln(x+1)=Ln(2)

ln [(3x-4)/(x+1)] = ln 2

(3x-4)/(x+1) = 2

3x - 4 = 2x + 2

x = 6

**Related Questions**

Math differentiation - 1. y = x^x 2. y = (sin^2xtan^4x)/(x^2+1)^2 3. y = x^(1/x...

Pre-Calculus - I need help solving this logarithmic equation: ln x + ln (x+3) = ...

Math - ln x^2(x+1)/x+2 Write in terms of ln(x), ln(x+1), and ln(x+2) is the ...

Help, Math. - Solve: 3e2x + 2 = 50 a. ln 8 b. ln 0.25 c. ln 14 d. 0.5ln 16...

Math - Which equation is equivalent to 3 ln 2 – ln 4 + 5 ln x = ln 3 + 2 ln 5? ...

Math - Which equation is equivalent to 3 ln 2 – ln 4 + 5 ln x = ln 3 + 2 ln 5? ...

pre cal - (1/3)LN27 + 2LNx = LN(2-x) i think i just need help getting started. I...

math - Express y as a function of x. C is a positive number. 3 ln y= 1/2ln (2x+1...

algebra - Not sure if I'm doing this right Ln(3x-4)-Ln(x+1)=Ln(2) My solution: ...

ALGEBRA - Contract the expressions. That is, use the properties of logarithms to...